Exploration of Students' Abilities in Solving Mathematical Literacy Problems on Geometry Material Using Polya's Steps - Ramalia, Tryza; Effie Efrida Muchlis; Edi Susanto; Cheng, Aw Yoke (International Journal of Geometry Research and Inventions in Education, 2024)
Students face challenges in understanding the minimum competency assessment (AKM) mathematical literacy questions, as they struggle to interpret and solve the problems effectively. This difficulty stems from their low comprehension of the questions and limited problem-solving skills, particularly when confronted with questions differing from the examples provided by the teacher. This study investigates students’ abilities to solve AKM mathematical literacy questions using Polya’s problem-solving steps. The research is descriptive with a qualitative approach, involving a population of all Grade VIII students at SMP 21 Bengkulu City during the 2023/2024 academic year. The sample consisted of 30 students from class VIII.3 and 30 from class VIII.6. Data collection included test and non-test (interview) methods, utilizing AKM-based test instruments and Polya step-guided problem-solving tasks. Results indicated that 44 students (73.33%) demonstrated low ability, 11 students (18.33%) showed medium ability, and only 5 students (8.33%) exhibited high ability in solving AKM literacy questions. Overall, students’ problem-solving skills were categorized as low, with notable difficulties in planning, executing, and reviewing solutions to mathematical problems.